2020
DOI: 10.3126/gaze.v11i1.26618
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impacts of Community-Based Home stay Ecotourism in Nepal

Abstract: Community-based home stay is one of the growing rural tourism enterprises. It has been a strong support for fostering ecotourism around the globe by uplift ing the local community. The present study was carried in Amaltari Madhawarti Homestay in the Nawalpur District of Nepal. The main aim of this study was to assess the environmental impacts of community-based home stay tourism. Twenty-four houses running home stays and same number of houses without home stay operation were surveyed and representative of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 32 publications
3
15
0
1
Order By: Relevance
“…Before the outbreak of COVID-19, many investors were attracted to the sector with an increased number of homestays openings due to the Visit Nepal 2020 campaign of the government ( Pandey and Dhakal, 2019 ). As of 2019, nearly 320 registered homestays and many other unregistered homestays were under-functioning in the village areas of Nepal ( Dahal et al, 2020 ). In the Terai Arc Landscape alone, WWF (2020) alone has supported a total of seventeen homestays.…”
Section: Discussionmentioning
confidence: 99%
“…Before the outbreak of COVID-19, many investors were attracted to the sector with an increased number of homestays openings due to the Visit Nepal 2020 campaign of the government ( Pandey and Dhakal, 2019 ). As of 2019, nearly 320 registered homestays and many other unregistered homestays were under-functioning in the village areas of Nepal ( Dahal et al, 2020 ). In the Terai Arc Landscape alone, WWF (2020) alone has supported a total of seventeen homestays.…”
Section: Discussionmentioning
confidence: 99%
“…In nature-based tourism areas, several policies have been studied and introduced, such as carrying capacity (Cuong et al, 2018), visitor impact management (Dangi and Gribb, 2018), and the limits of acceptable changes (Komsary et al, 2018). Various studies highlight the importance of measuring the magnitude of the environmental impact that tourists are aware of and understand when traveling Dahal et al, 2020). Initial studies have explored visitor behaviors, desires, and expectations, in addition to research into outdoor recreation habits and satisfaction with outdoor recreation experiences.…”
Section: Environmental Impactmentioning
confidence: 99%
“…Early research about visitor perceptions of environmental impacts was generally limited, as concluded by Lucas (1979). There is a small but growing amount of research on tourists' attitudes about environmental impacts; still, researchers face challenges due to a lack of solid research on this topic (Dahal et al, 2020;KC et al, 2020).…”
Section: Environmental Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…The sustainability of tourist destinations is dependent upon environmental concerns and conservation of local stakeholders [42,68]. Construction of homestay accommodations and the operation should attach importance to eco-friendliness and long-term sustainability [69].…”
Section: Methodsmentioning
confidence: 99%